The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/aac.46.2.315-320.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bacilysocin, a Novel Phospholipid Antibiotic Produced by Bacillus subtilis 168

Abstract: We have found a novel phospholipid antibiotic (named bacilysocin) which accumulates within (or associates with) the cells of Bacillus subtilis 168 and determined the structure by nuclear magnetic resonance and mass spectrometry analyses. The structure of bacilysocin elucidated was 1-(12-methyltetradecanoyl)-3-phosphoglyceroglycerol. Bacilysocin demonstrated antimicrobial activity, especially against certain fungi. Production of bacilysocin commenced immediately after growth ceased and before the formation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 13 publications
(3 reference statements)
0
86
1
Order By: Relevance
“…Furthermore, HMBC correlations from H-1a (δ 4.16) and H-1b (δ 4.09) to the carbonyl carbon at C-1 (δ 174.0) confirmed the ester linkage in the molecule. The presence of phosphate group was secured from the careful comparison of obtained NMR data with those reported (Tamehiro et al, 2002). The absolute configuration at C-2 was presumed to be R (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, HMBC correlations from H-1a (δ 4.16) and H-1b (δ 4.09) to the carbonyl carbon at C-1 (δ 174.0) confirmed the ester linkage in the molecule. The presence of phosphate group was secured from the careful comparison of obtained NMR data with those reported (Tamehiro et al, 2002). The absolute configuration at C-2 was presumed to be R (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…Bacilysocin, a novel lysophosphatidylglycerol, isolated from Gram-positive bacteria (Bacillus subtilis), is reported to possess antimicrobial activity against bacteria and certain fungi (Tamehiro et al, 2002). One recent study showed that lysophosphatidylglycerols inhibit β-glucuronidase and can be used for prevention of colon and bladder cancers and also as drugs (oral or topical), health foods, and cosmetics for inhibiting unpleasant body odor (Shiojiri, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these the amino acid sequence of the product (YkoN) of ykoN has a weak homology with that of ugtP (ypfP) that is responsible for the synthesis of glucosylated diacylglycerates in this organism 5,7) , however, YkoN is found not to be involved in the synthesis of glucosylated diacylglycerates. The amino acid sequence of YkoN has a pentapeptide sequence (Gly-Gly-Ser-Met-Gly) that is compatible with the Gly/Ala-X-Ser-X-Gly motif of lipase/esterase as those shown among the microbial lipolytic enzymes, LipA, LipB, YtpA, and p-nitrobenzyl esterase (PnbA) of B. subtilis and lysophospholipase L2 (PldB) and Aes of E. coli [8][9][10][11][12][13][14] . We have purified His- Tagged YkoN and have shown that YkoN has an esterase activity.…”
Section: Introductionmentioning
confidence: 99%